A prebiotic intervention improves mood in everyday life in healthy women but not in men: Exploratory results from a larger double-blind placebo controlled cross-over study - Koen Hogenelst; Tanja Krone; Boukje Eveleens Maarse; Ines Warnke; Jessica Snabel; Tim J. van den Broek; Frank Schuren; Matthijs Moerland; Femke P.M. Hoevenaars (Brain, Behavior, & Immunity - Health)
Prebiotic dietary fiber (PDF) may reduce feelings of stress or improve mood in healthy individuals. Yet gut intervention studies that focus on mood in daily life are lacking and few studies include extensive biological sample analyses to gain mechanistic insights. As part of a larger randomized placebo-controlled crossover study including healthy individuals, we explored the effects of 12 weeks of PDF (acacia gum and carrot powder) on everyday mood, as measured with ecological momentary assessment (EMA). Microbiome composition and levels of microbial metabolites, endocrine, and inflammatory markers were determined prior to and after both intervention phases. Fifty-four participants completed the study. The intervention significantly increased daily positive affect (PA) and reduced daily negative affect (NA) in female but not male participants. The intervention-induced reduction in NA was associated with an increase in microbial diversity in female participants. The intervention did not significantly affect levels of fecal short chain fatty acids, cortisol, and inflammatory markers. This is one of the first studies to show that a dietary fiber intervention can positively alter mood as it is experienced in everyday life. Overall, our findings may stimulate more targeted gut-microbiome interventions and detection of its mental health effects in real life.